2022
DOI: 10.52970/grhrm.v2i1.155
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Work Arrangements, Work Environment, and Job Stress on Job Satisfaction and Turnover Intention

Abstract: This study was conducted to analyze the influence of Alternative work arrangementss, work environment, and job stress on job satisfaction. The object of this research is millenial bankir with a total sample of 120 employees and data collection use online survey. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results of this study indicate that Alternative work arrangementss, job stress have a negative significant effect on job satisfaction, work environment has a positive significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The current finding indicated that employee are least satisfied with salary and benefits the finding is consistent with (Kuo, Lin, & Li, 2014;Situmorang & Wardhani, 2022) . Salary was the dominant factor for determining the level of job satisfaction, intention to leave and consideration of returning (Mawardi, 2022;Pratama, Suwarni, & Handayani, 2022;Chavadi, Sirothiya, & MR, 2022). Current study showed that the supervision was also affect job satisfaction.…”
Section: Discussionmentioning
confidence: 80%
“…The current finding indicated that employee are least satisfied with salary and benefits the finding is consistent with (Kuo, Lin, & Li, 2014;Situmorang & Wardhani, 2022) . Salary was the dominant factor for determining the level of job satisfaction, intention to leave and consideration of returning (Mawardi, 2022;Pratama, Suwarni, & Handayani, 2022;Chavadi, Sirothiya, & MR, 2022). Current study showed that the supervision was also affect job satisfaction.…”
Section: Discussionmentioning
confidence: 80%
“…Job performance evaluation consists of studying and analyzing employees' performance of their work and observing their behavior and actions during work to judge the extent of their success and the level of their abilities in carrying out Sokara Public Hospital Institution. The study (Karim, 2022) also showed that the pressure resulting from work may negatively affect the performance of employees, and this can negatively affect the company's performance in general, as well as the study (Mawardi, 2022) which showed that alternative work styles and a good working environment reduce intention to Action, while pressures resulting from work increase the intention to act and affect performance in general. Ben Alla (2022) study also showed that work pressures represent part of the employees' performance tasks, and that the relationship of the dimensions of work pressures to employees' performance is related to the workload, the work environment, and the organizational structure, in the Directorate of Electricity and Gas Distribution in Timiun, one of the subsidiaries of the Sonlemgaz Distribution Company for Morocco, Oran.…”
Section: Job Performancementioning
confidence: 84%
“…This commitment, in turn, can lead to improved performance and outcomes. Kessi et al (2022); Mawardi (2022) research highlights the positive impact of transformational leadership on organizational commitment and provides insights into its motivational and inspirational aspects.…”
Section: Role Of Transformational Leadership On Financial Management ...mentioning
confidence: 99%